DriVE-MATH: Reimagining Education - Pinto Carla M.A; Mendonça Jorge (De Gruyter, 2022)
In this paper we provide a description of the project DrIVE-MATH, highlighting the main goals, intellectual outputs, outcomes, the involved partners, and activities and reports from the three-years' project. At the end we discuss the impact of the new proposed Education models at various levels, from students, to HEIs, to stakeholders.